Urinary Angiotensinogen as a Biomarker of Nephropathy in Childhood. (9th August 2011) - Urushihara, Maki; Kagami, Shoji
Abstract : While most circulating angiotensinogen (AGT) is synthesized in the liver, the kidneys also produce AGT. Recently, we reported that urinary AGT is mainly originated from AGT. Using newly developed human AGT ELISA, we measured urinary AGT levels in chronic glomerulonephritis (GN) patients and patients with type 1 diabetes in childhood. Urinary AGT level was positively correlated with diastolic blood pressure, urinary albumin, urinary protein levels, and urinary occult blood in chronic GN patients. Furthermore, urinary AGT level was significantly increased in chronic GN patients not treated with renin-angiotensin system (RAS) blockers compared with control subjects. Importantly, patients treated with RAS blockers had a marked attenuation of this increase. Also, urinary AGT level was significantly higher in patients with diabetic nephropathy in the premicroalbuminuric phase than in control subjects. These results suggest that urinary AGT reflects intrarenal RAS status in chronic GN and may be an early marker of diabetic nephropathy.